The effect of Sesuvium portulacastrum for reducing inorganic nitrogen pollution in coastal mariculture wetland - Liu, Kai; Gao, Wei; Yu, Zhenzhen; Hu, Yongchao; Zuo, Ming; Sun, Chen; Zou, Xiaotao; Wang, Lizhi (Frontiers in Marine Science, 2024)
Mariculture ponds are essential components of the coastal wetland, which are often criticized by eutrophication risk for the dissolved inorganic nitrogen (DIN) input to the coastal zone by the culture tailwater. However, the reduce of this DIN pollution was difficult because the tailwater is hard to collect and the treatment is inefficient and expensive. Sesuvium Portulacastrum is a coastal vegetation which has high efficiency in DIN absorption from the seawater and sediment. In this study, we use Sesuvium Portulacastrum as a tool species to study the control behavior of the DIN in mariculture ponds wetland. The change trend of DIN in pond water and benthic species in pond sediment was investigated. The results showed that Sesuvium Portulacastrum reduced NH4+, NO3-, and NO2- in the pond water by 83.21%, 95.22%, and 91.32%, respectively. The species number of benthic organisms was enhanced from 2 to 5 and the species structure was more optimized in Sesuvium Portulacastrum pond than control pond. At the end of the experiment, eutrophication indicator species (Capitella capitata) was disappeared in the Sesuvium Portulacastrum pond. Those suggest that the coastal vegetation (Sesuvium Portulacastrum) have great potential to eliminate DIN pollutants in mariculture pond wetland.